Of blood and belonging: the practice of antiretroviral treatment among HIV-positive youth in South Africa's Eastern Cape - Vale, B (2015)
HIV-positive adolescents are an increasingly numerous and challenging population in the South African HIV/AIDS epidemic. Their access to, and retention in, ART care has become a pressing public health concern. Comprised of four journal articles, this thesis explores the practice of antiretroviral treatment (ART) among a cohort of HIV-positive adolescents (age 10–19) in South Africa's Eastern Cape. By 'practice', I mean the volatile, situated and relational 'work' that goes into young people's everyday achievement of ART — into consuming daily medication, regularly attending health appointments, and participating in HIV programmes. Through an exploration of the ways in which some HIV-positive adolescents use, appropriate, or reject ART care; this thesis contributes to a much-needed evidence-base on the needs and survival strategies of adolescent ART users. Data for this study was gathered through eight months of multi-method ethnographic fieldwork with 23 HIV-positive youth, their families, and local health workers. The findings elucidate adolescent ART as a complex (and often volatile) form of social incorporation, through which young people negotiate survival, care and moral connection in contemporary South Africa. Enrolling in ART meant being encompassed into a (often hierarchical) set of social relationships, through which adolescents sought belonging, recognition and protection, amid profound insecurity. Through ART and its associated programmes, adolescents and their families attempted to strengthen familial ties, appeal to powerful patrons, petition for care, and access basic resources. Yet these pursuits were often deeply ambivalent, as discipline, blame, and resentment often came encased in the terms of care. At the crux of each article is an attempt to understand how adolescents, often alongside their families, negotiated both the social stakes and possibilities of ART. Through these discussions, we might better be able to grasp the fragility and complexity of young people's retention in ART.